Designing Visual Identity as An Asset for Photo Cabin Rebranding - Iswanto, Rendy (VCD: Journal of Visual Communication Design, 2022)
Photo Cabin is one of the many photo corner businesses in Surabaya. With the high number of competition and the high demands of photo corner services at Surabaya, Photo Cabin must be able to attract more clients to survive the competition. In order to achieved brand loyalty, a good brand image is needed which is formed from a good brand identity. Charles Kwee as the owner of Photo Cabin has given the fact that when Photo Cabin was established the Brand Identity was not designed properly due to the various limitations. Therefore, designing visual identity as an Asset for Rebranding efforts for Photo Cabin is needed in order to survive the high competition rate and fulfilling the high demand of photo corner services at Surabaya. The design method used in this design are Design Thinking method. Keywords: Brand, Brand Loyalty, Brand Image, Brand Identity, Design Thinking, Photo Corner, Photo Cabin, Rebranding